Integrasi Program Tahfidz dengan Sekolah Formal di Pondok Pesantren Anak - Faqih, Ngabdul (Institut Agama Islam Negeri Kendari, 2020)
This article aims to present the analysis of the integration of the tahfidz program with formal schools in the Islamic boarding schools focusing on the Holy Qur'an memorization in East Java, Indonesia. This phenomenology study used data gathered from interviews, observation and documentation. The results of data analysis indicate that the model of the integration of the tahfidz program from Islamic boarding schools into the madrasah ibtida'iyyah (MI) curriculum is done by adding Qur'anic subjects to the Hadith with the allocation of two lesson hours per week which also requires students to memorize the Qur'an in accordance with the target to support the tahfidz program in Islamic boarding schools. It is also found that the the advantages of the tahfidz program integration model is to accelerate students' ability to memorize because of the similarity of the tahfidz method used as well as the presence of additional subjects in the curriculum that support the tahfidz program.